Brazing Al2O3 to 4J42 using Ag–Cu–Ti/Cu/BNi-2 composite fillers with different thicknesses of Cu interlayer. Issue 6 (15th March 2023) - Zhu, Qianying; Cai, Yangyang; Liu, Zheng; Gong, Keqian; Wang, Zhentao; Li, Litao; Zhang, Yong
Abstract: A two-step brazing process was used to braze Al2 O3 and 4J42 with an Ag–Cu–Ti/Cu/BNi-2 composite filler with varying Cu interlayer thicknesses. The influences of the Cu interlayer thickness on the microstructure and mechanical properties of Al2 O3 /4J42 joints were thoroughly investigated. The results show that the main products between the Al2 O3 ceramic and the filler are Cu2 Ti4 O, Ti–O and Al-based compounds, which are visible as a micron-scale layer. The Cu interlayer thickness determines the microstructure and mechanical properties of the joints. When the Cu interlayer thickness is 50 μm, it exhibits a discontinuous island-like structure and cannot prevent the diffusion of Ti, which results in a significant thinning of the reaction layer and a pronounced lowering of the shear strength. When the Cu interlayer thickness increases to 100 μm, the joint exhibits maximum shear strength because Ti diffusion is sufficiently prevented and the residual stress is also released by the Cu interlayer. As the Cu interlayer thickness is increased further (up to 150 μm or 200 μm), the diffusion of Ti can be completely prevented. However, the thicker Cu interlayer with low mechanical strength and large strain during the brazing process deteriorates the strength of the joint.